THE INFLUENCE OF DISCIPLINE IN LEARNING AND EDUCATIONAL INTERACTIONS ON STUDENT LEARNING OUTCOMES AT SMK - Mohamad Muspawi (Dinasti Publisher, 2020)
This research aims at knowing the influence of discipline in learning and educational interactions partially and simultaneously on student learning outcomes at SMK Negeri 1 Jambi City. This research used descriptive quantitative method. In terms of data collection, this research used instruments in the form of questionnaires distributed to students and student grades. The population used in this study were 122 students in class XI and 67 students were selected as samples. The sample calculation was done by interpolation, simple random sampling was used in the distribution. This research used simple regression analysis and multiple regression analysis as the data analysis techniques. The result shows that: (1) There is a partially significant influence between discipline in learning on the results of 0.444, then Ho was rejected and Ha was accepted; (2) There is a partially significant influence between educational interactions on student learning outcomes of 0.320, then Ho is rejected and Ha is accepted; and (3) There is a significant simultaneous influence between discipline in learning and educational interaction on student learning outcomes of 0.602. Hence, it can be concluded that discipline in learning and educational interactions both have an influence on student learning outcomes. Researchers suggest that teachers should be able to emerge student discipline in learning, make better interactions, encourage students to actively interact during the learning process.